2022
DOI: 10.3390/ijms232314827
|View full text |Cite
|
Sign up to set email alerts
|

Combined Administration of Pravastatin and Metformin Attenuates Acute Radiation-Induced Intestinal Injury in Mouse and Minipig Models

Abstract: Radiation-induced gastrointestinal (GI) damage is one of the critical factors that serve as basis for the lethality of nuclear accidents or terrorism. Further, there are no Food and Drug Administration-approved agents available to mitigate radiation-induced intestinal injury. Although pravastatin (PS) has been shown to exhibit anti-inflammatory and epithelial reconstructive effects following radiation exposure using mouse and minipig models, the treatment failed to improve the survival rate of high-dose irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…In animal experiments, Kim et al [ 137 ] used a combination of PS and MF in a minipig model and found that the combined treatment could attenuate radiation-induced intestinal histological damage, significantly increase the survival rate of the lethal dose radiation model, and achieve better therapeutic effects. Najafi et al [ 138 ] investigated the possible radioprotection of the ileum and colon in rats using a combination of melatonin and metformin.…”
Section: Treatment Strategy Of Radiation-induced Intestinal Injurymentioning
confidence: 99%
“…In animal experiments, Kim et al [ 137 ] used a combination of PS and MF in a minipig model and found that the combined treatment could attenuate radiation-induced intestinal histological damage, significantly increase the survival rate of the lethal dose radiation model, and achieve better therapeutic effects. Najafi et al [ 138 ] investigated the possible radioprotection of the ileum and colon in rats using a combination of melatonin and metformin.…”
Section: Treatment Strategy Of Radiation-induced Intestinal Injurymentioning
confidence: 99%
“…[5,6] Exposure of small intestine to ionizing radiation can lead to serious gastrointestinal dysfunction, such as vomiting, abdominal pain, diarrhea, infection, perforation, and even death. [7] To date, there are few effective countermeasures for intestinal radioprotection in clinical.…”
Section: Introductionmentioning
confidence: 99%
“…Small intestine is one of the most radiation-sensitive organs with large organ volume and is a major injury tissue during abdominal and pelvic radiation therapy [5,6]. Exposure of small intestine to ionizing radiation can lead to serious gastrointestinal dysfunction, such as vomiting, abdominal pain, diarrhea, infection, perforation, and even death [7]. To date, there are few effective countermeasures for intestinal radioprotection in clinical.…”
Section: Introductionmentioning
confidence: 99%